First crotoxin-like phospholipase A2 complex from a New World non-rattlesnake species: Nigroviriditoxin, from the arboreal Neotropical snake Bothriechis nigroviridis. (January 2015) - Lomonte, Bruno; Mora-Obando, Diana; Fernández, Julián; Sanz, Libia; Pla, Davinia; María Gutiérrez, José; Calvete, Juan J.
Abstract: Bothriechis nigroviridis is an arboreal Neotropical pitviper found in Costa Rica and Panamá. A previous proteomic profiling of its venom revealed the presence of proteins with homology to the A and B subunits of crotoxin/Mojave toxin, a heterodimeric phospholipase A2 (PLA2 ) complex only described in rattlesnake venoms (genera Crotalus and Sistrurus ). The native crotoxin-like heterodimer, named nigroviriditoxin, and its A and B subunits were isolated in the present work, and the complete amino acid sequence of the B subunit was determined. The purified A and B components were demonstrated to form a complex when reconstituted under native conditions. Nigroviriditoxin presents features similar to crotoxin, albeit displaying lower toxicity: the A component decreases the PLA2 activity of the B component, and increases its lethal potency in mice. Also in similarity to crotoxin B, nigroviriditoxin B induces myonecrosis. Its 122 amino acid sequence presents 81% identity with crotoxin B. Accordingly, nigroviriditoxin B was cross-recognized by equine antibodies from a Crotalus durissus terrificus antivenom. Phylogenetic analysis shows that the novel PLA2 from B. nigroviridis venom is basal to the branch including all the homologous PLA2 enzymes described in rattlesnakes, and more distant from PLA2 s from Bothriechis species. Nigroviriditoxin is the first heterodimeric PLA2 complex found in a non-rattlesnake, Neotropical viperid venom, which displays structural, functional, and immunochemical similarities to crotoxin. The present findings are compatible with the existence of the particular structural trait of crotoxin-like molecules in New World pitvipers before the split of the Meso-South American and the Nearctic clades. Graphical abstract: Highlights: Bothriechis nigroviridis is an arboreal Neotropical pitviper found in Central America. Its venom contains proteins homologous to crotoxin A and B subunits of rattlesnake venoms. These A and B subunits form a complex, nigroviriditoxin, similar to crotoxin. Nigroviriditoxin is the first heterodimeric PLA2 complex found in a non-rattlesnake, Neotropical viper.